Monolithic Perovskite/Silicon Tandems with >28% Efficiency: Role of Silicon‐Surface Texture on Perovskite Properties. (9th December 2022) - De Bastiani, Michele; Jalmood, Rawan; Liu, Jiang; Ossig, Christina; Vlk, Aleš; Vegso, Karol; Babics, Maxime; Isikgor, Furkan H.; Selvin, Anand S.; Azmi, Randi; Ugur, Esma; Banerjee, Swarnendu; et al.
Abstract: Textured silicon wafers used in silicon solar cell manufacturing offer superior light trapping, which is a critical enabler for high‐performance photovoltaics. A similar optical benefit can be obtained in monolithic perovskite/silicon tandem solar cells, enhancing the current output of the silicon bottom cell. Yet, such complex silicon surfaces may affect the structural and optoelectronic properties of the overlying perovskite films. Here, through extensive characterization based on optical and microstructural spectroscopy, it is found that the main effect of such substrate morphology lies in an altering of the photoluminescence response of the perovskite, which is associated with thickness variations of the perovskite, rather than lattice strain or compositional changes. With this understanding, the design of high‐performance perovskite/silicon tandems is rationalized, yielding certified power conversion efficiencies of >28%. Abstract : The texturing of crystalline silicon results in uniformly distributed pyramids. This is a key strategy to reduce the reflective losses and increase the current output of solar cells. Here, the influence of different texturing sizes is investigated on the performance and optoelectronic properties of monolithic perovskite/silicon tandems. The optimal texturing conditions to achieve devices with a certified power conversion efficiency above 28% are reported.